Свято-Покровський жіночий монастир у місті Яворові (1621–1691): організаційний розвиток та виклики часу - Цебенко, Андрій; Tsebenko, Andriy (Видавництво Львівської політехніки, 2020)
Досліджено становлення та організаційний розвиток православного жіночого монашого осередку в XVII ст. у місті Яворові (сьогодні – Львівська область). Вказано виклики, які впродовж сімдесяти задокументованих років діяльності монастиря вимушена була долати чернеча громада. Звернено увагу на роль влади в різних обставинах діяльності монастиря, а також роз’яснено дискусійні формулювання.

Throughout history, Ukrainian monasteries have played an extraordinary role in the choice of spiritual, cultural, and sometimes political ways of the Ukrainian community, spreading Christian morality, affirming the Church and its doctrines. The article deals with the organizational development of one of the Ukrainian Orthodox women’s monasteries in the 17th century. in the Yavoriv district (Crown of Poland) in the author’s vision. Various hypotheses from the history of the monastery, including date and location, are stated. Most researchers believe that the Holy Mother’s Convent in Yavoriv was founded in 1621. There are some differences regarding the location of the first nun’s settlement in researchers: some claim that they settled near the Assumption of the Blessed Virgin, while others were located near the church. St. incl. Yuri (within the city ramparts), and only later moved to the Great Suburbs. The challenges that the monastic community had to overcome were noted. In particular, the fire of 1636 and the need for a new foundation. The two homes where the nuns temporarily lived were burned down and the sisters were left without accommodation. To the aid of the monastic community came a Yavoriv woman from an ancient priestly family, Zhugaevich (Zagayevich), Margarita Grytsykivna (Dyshkevich by her husband). And also about the seizure of property by the descendants of the founder Abbot Makrina by her relatives after her death and lawsuits. The names of the nuns, the abbot-sponsors of Makaria and Makrina, as well as the educational institution for orphan girls at the monastery are mentioned. A number of documents have been studied, such as the privileges of kings and the will of the abbot-sponsor. The local government and the Polish kings have repeatedly confirmed the monastic rights to land and tax exemption. The Covenant provides guidance, teachings, and reflections that are written on the points and addressees and give a lot of interesting information about the life of the monastery, some rules and instructions to the sisters how to behave and organize a monastic community. Some scholars have explored the use of the definition of “Basilian” in relation to Orthodox monasteries.
The holy-intercession women’s monastery in Yavoriv (1621–1691): organizational development and the challenges of time
Keywords: монастир; православ’я; жіноче чернецтво; ігуменя; привілеї; monastery; orthodoxy; female monasticism; abbot; privileges; 94; 271.2-788-055.2](477.83-21)"1621/1691"